Islam as a Religion, Civilization and Science - Raden Fadli Daulay; Wildan Murtadho; Mohammad Al Farabi; Zulkifli Tanjung (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Islam and civilization are a unity that cannot be separated. Since its presence, Islam has carried the concept and mission of civilization that is inherent in itself. Islamic civilization is rooted in din which comes from Allah's revelation. That is why civilization is commonly known as tamaddun or madaniyyah, because it originates from the dn. Then the high expression of Islamic civilization in the history of human civilization got its place in Yathrib which later turned into Medina. From the relation of modernism to the current world phenomenon, of course, religion faces the challenges of Modernism. Religion is like humanity itself, and is essentially spiritual in origin. It symbolizes a resealed series of divine instructions to various prophets and apostles of Allah to direct mankind in the right direction.